Antibody detection against Kunitz-type protein in Fasciola hepatica experimentally infected sheep using enzyme-linked immunosorbent assay (ELISA) - María Ahumada; Agustina Godino; Lorena Guasconi; Carla Deheza; Marilla Amaranto; Cesar Iván Pruzzo; Gabriel Vitulli-Moya; Laura Chiapello; María Elena Carrizo; José Luis Barra; Laura Cervi (International Journal of Veterinary Science and Medicine, 2023)
ABSTRACTFasciolosis is a parasitic disease considered as emerging and neglected by the WHO. Sheep are highly susceptible to this disease, and affected flocks experience decreased productivity due to increased mortality, and the reduced quality of their products, such as wool and meat. To effectively control this disease, reliable and early diagnosis is essential for making decisions regarding antiparasitic application and/or the removal of affected animals. Currently, the diagnosis of F. hepatica in sheep relies on the detection of parasite eggs in faeces, a method that becomes reliable from week 10 post-infection. Consequently, there is a need for earlier diagnostic tools based on immune response. However, obtaining antigens for antibody detection has proven to be difficult and expensive. The aim of this study was to evaluate members of the Kunitz protein family of F. hepatica expressed in the form of a fusion protein in the serological diagnosis of F. hepatica in sheep. The performance of three recombinant F. hepatica Kunitz-type inhibitors (FhKT1.1, FhKT1.3, and FhKT4) was compared with a synthetic Kunitz-type peptide (sFhKT) in sera from sheep experimentally infected with F. hepatica, using an ELISA. Of these, FhKT1.1 showed the most promising diagnostic indicators, exhibiting high precision and low cross-reactivity, and thus potential for standardized production. The results of our study demonstrated that the application of FhKT1.1 is a valuable tool for early-stage diagnosis of F. hepatica in sheep. Such an early diagnosis can aid in implementing timely interventions and effectively managing the disease in sheep populations.